Verbal and verbal-visual logico-semantic relations in picturebooks: an English-Portuguese parallel corpus study - Pagano, Adriana Silvina (2018)
This article presents and explores a methodology to analyze verbal and verbal-visual logico-semantic relations (LSRs) in picturebooks originally written in English and their translations into Brazilian Portuguese. Drawing on systemic-functional theory (Halliday & Matthiessen, 2014) and on Visual Grammar (Kress & van Leeuwen, 2006), verbal and visual text in picturebooks was annotated and analyzed according to the LSRs identified in them. Results showed differences between the type of LSRs that tend to occur most frequently in verbal-visual texts and in clause complexes: while Expansion_Extension is the most frequent verbal-visual LSR in both the source text and the translated text, Projection_Locution is the most frequent LSR in clause complexes, in the source and translated texts as well. The study contributes a proposal to categorize LSRs in verbal text and LSRs in visual and verbal text that proves to be fully operational for annotation purposes and text analysis.